2021
DOI: 10.1002/adsu.202100267
|View full text |Cite
|
Sign up to set email alerts
|

Fast Scalable Synthetic Methodology to Prepare Nanoflower‐Shaped Bi/BiOClxBr1−x Heterojunction for Efficient Immobilized Photocatalytic Reactors under Visible Light Irradiation

Abstract: the photoinduced charge carriers. [8][9][10] Besides, it is highly desirable to achieve these goals using earth-abundant materials and a cost-effective, energy-efficient, and scalable preparation strategy for large-scale photocatalytic systems.Recently, bismuth oxyhalides (BiOXs, X = Cl, Br, and I) have demonstrated excellent photocatalytic activity under sunlight irradiation due to their distinct characteristics such as indirect bandgap, excellent electronic configuration, unique layered structures, high dipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Notably, the Ti 2p peak intensity of Ti-Bi NSs was significantly weaker than that of Bi 4 Ti 3 O 12 , indicating a large amount of Ti peeled off from the Bi 4 Ti 3 O 12 material, consistent with the doping characteristics of Ti-Bi NSs. [36,37] The CO 2 reduction performance of Ti-Bi NSs electrocatalyst was investigated by using a flow cell in a 1.0 M KOH solution (Figure S8, Supporting Information). To deeply understand the effect of ultrathin Ti-Bi NSs on the catalytic CO 2 electroreduction, Bi NSs, and Bi powder were selected as a comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the Ti 2p peak intensity of Ti-Bi NSs was significantly weaker than that of Bi 4 Ti 3 O 12 , indicating a large amount of Ti peeled off from the Bi 4 Ti 3 O 12 material, consistent with the doping characteristics of Ti-Bi NSs. [36,37] The CO 2 reduction performance of Ti-Bi NSs electrocatalyst was investigated by using a flow cell in a 1.0 M KOH solution (Figure S8, Supporting Information). To deeply understand the effect of ultrathin Ti-Bi NSs on the catalytic CO 2 electroreduction, Bi NSs, and Bi powder were selected as a comparison.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, extensive reports have demonstrated that semiconductor photocatalysts can degrade a wide range of inorganic and organic pollutants. [183][184][185][186][187] What's more, the functional CDs have also been regarded as promising modifiers that can be utilized for decorating photocatalysts to improve their degradation performance, because of the multiple roles such as accelerating carriers separation, increasing spectral absorption, regulating energy band, and providing adsorption sites. [188] This section will introduce the applications of the CDs-based photocatalysts in photocatalytic degradation of typical inorganic and organic gaseous contaminants (NO x and VOCs) and explore the mechanism for enhancing the hybrid nanocomposite performance.…”
Section: Carbon Dots-based Photocatalysts For Air Pollutants Removalmentioning
confidence: 99%
“…14–18 Overall, due to the properties of ferrite magnetic nanomaterials and hexaferrite (M-type), they can be used for the adsorption of various metals ions, cationic and anionic dyes from wastewater. 19–23…”
Section: Introductionmentioning
confidence: 99%